2012
DOI: 10.1519/jsc.0b013e31826791a7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Squat Depth and Barbell Load on Relative Muscular Effort in Squatting

Abstract: Resistance training is used to develop muscular strength and hypertrophy. Large muscle forces, in relation to the muscle's maximum force-generating ability, are required to elicit these adaptations. Previous biomechanical analyses of multi-joint resistance exercises provide estimates of muscle force but not relative muscular effort (RME). The purpose of this investigation was to determine the RME during the squat exercise. Specifically, the effects of barbell load and squat depth on hip extensor, knee extensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 23 publications
5
89
1
1
Order By: Relevance
“…It is important to consider the stimulus of adjacent joints; therefore, we plotted ankle dorsiflexion kinematics and kinetics in Figures and , and descriptive statistics are provided as additional information for the ankle, in addition to L5/S1 NJM. In a NARROW squat, plantar flexor relative muscular effort is high and peaks toward the end of the ascent . These kinetic changes correspond with COP movement shifting toward the forefoot, albeit more so in NARROW (Figure ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is important to consider the stimulus of adjacent joints; therefore, we plotted ankle dorsiflexion kinematics and kinetics in Figures and , and descriptive statistics are provided as additional information for the ankle, in addition to L5/S1 NJM. In a NARROW squat, plantar flexor relative muscular effort is high and peaks toward the end of the ascent . These kinetic changes correspond with COP movement shifting toward the forefoot, albeit more so in NARROW (Figure ).…”
Section: Discussionmentioning
confidence: 95%
“…In a NARROW squat, plantar flexor relative muscular effort is high and peaks toward the end of the ascent. 27 These kinetic changes correspond with COP movement shifting toward the forefoot, albeit more so in NARROW ( Figure 3). Swinton et al 6 results demonstrated that a narrower squat position produced significantly higher ankle NJM than wider position, while our results did not significantly differ but demonstrated small to moderate effects in favor of the NARROW position (additional information, Table 2).…”
Section: Frontal Plane Stimulusmentioning
confidence: 88%
See 1 more Smart Citation
“…Surface EMG has been widely used for assessment of muscle activities during squat, and it has been shown that the EMG activities of the muscles increased by increasing the loads during squatting in different studies [2023]. Bryanton et al [24] studied the biomechanical analysis and relative muscular effort during squat while increasing the barbell load from 50% to 90% of 1RM but did not use EMG to determine the muscle activities and more importantly the maximal loading that we expect to see the kinetic and muscular activity changes. Therefore, we aimed to see the kinematic and muscular activity changes while we increase the loads from 80% to 90% and finally 100% of 1RM squatting.…”
Section: Introductionmentioning
confidence: 99%
“…Generally when the clean is performed and the athlete propels the barbell upward, they flex at the lower body joints to lower the Centre of Mass (COM) so that the barbell can be caught on the shoulders at a reduced height. As repetitions increased and the athletes became more fatigued, it is possible that they adopted the strategy to lower the COM through less hip flexion and more ankle dorsiflexion to reduce energy demand required to rise from a squat with the hips in a more extended position [23]. This altered lifting strategy is likely to reduce the effectiveness of the exercise.…”
Section: Discussionmentioning
confidence: 99%